Systematic Literature Review: Exploring Antecedents And Consequences Of Spiritual Leadership - Wadud, Abdul; Agustina, Tri Siwi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study conducted a systematic literature review on spiritual leadership in an organizational context. From 539 articles identified through the Scopus database, 21 articles were selected based on the criteria of year of publication, relevance to business management and accounting, and the keyword